Alcohol Intake and Abnormal Expression of Brf1 in Breast Cancer. (31st October 2019) - Huang, Chenghao; Zhang, Yanmei; Zhong, Shuping
Abstract : Breast cancer is the most common malignant disease of females. Overall, one woman in every nine will get breast cancer at some time in her life. Epidemiological studies have indicated that alcohol consumption has most consistently been associated with breast cancer risk. However, the mechanism of alcohol-associated breast cancer remains to be addressed. Little is known about the effects of alcohol consumption on Brf1 (TFIIIB-related factor 1) expression and RNA Pol III gene (RNA polymerase III-dependent gene) transcription, which are responsible for protein synthesis and tightly linked to cell proliferation, cell transformation, and tumor development. Emerging evidences have indicated that alcohol induces deregulation of Brf1 and Pol III genes to cause the alterations of cell phenotypes and tumor formation. In this paper, we summarize the progresses regarding alcohol-caused increase in the expression of Brf1 and Pol III genes and analysis of its molecular mechanism of breast cancer. As the earlier and accurate diagnosis approach of breast cancer is not available yet, exploring the molecular mechanism and identifying the biomarker of alcohol-associated breast cancer are especially important. Recent studies have demonstrated that Brf1 is overexpressed in most ER+ (estrogen receptor positive) cases of breast cancer and the change in cellular levels of Brf1 reflects the therapeutic efficacy and prognosis of this disease. It suggests that Brf1 may be a potential diagnosis biomarker and a therapeutic target of alcohol-associated breast cancer.